Step
*
1
1
of Lemma
bag-map-combine
1. A : Type
2. B : Type
3. C : Type
4. g : A ⟶ bag(B)
5. f : B ⟶ C
6. as : A List
7. bs : A List
8. permutation(A;as;bs)
⊢ bag-map(f;⋃x∈bs.g[x]) = ⋃x∈bs.bag-map(f;g[x]) ∈ bag(C)
BY
{ (ThinVar `as' THEN ListInd (-1) THEN Reduce 0 THEN Auto)⋅ }
1
1. A : Type
2. B : Type
3. C : Type
4. g : A ⟶ bag(B)
5. f : B ⟶ C
⊢ bag-map(f;⋃x∈[].g[x]) = ⋃x∈[].bag-map(f;g[x]) ∈ bag(C)
2
1. A : Type
2. B : Type
3. C : Type
4. g : A ⟶ bag(B)
5. f : B ⟶ C
6. u : A
7. v : A List
8. bag-map(f;⋃x∈v.g[x]) = ⋃x∈v.bag-map(f;g[x]) ∈ bag(C)
⊢ bag-map(f;⋃x∈[u / v].g[x]) = ⋃x∈[u / v].bag-map(f;g[x]) ∈ bag(C)
Latex:
Latex:
1.  A  :  Type
2.  B  :  Type
3.  C  :  Type
4.  g  :  A  {}\mrightarrow{}  bag(B)
5.  f  :  B  {}\mrightarrow{}  C
6.  as  :  A  List
7.  bs  :  A  List
8.  permutation(A;as;bs)
\mvdash{}  bag-map(f;\mcup{}x\mmember{}bs.g[x])  =  \mcup{}x\mmember{}bs.bag-map(f;g[x])
By
Latex:
(ThinVar  `as'  THEN  ListInd  (-1)  THEN  Reduce  0  THEN  Auto)\mcdot{}
Home
Index